In vitro and in vivo synergistic effect of chrysin in combination with colistin against Acinetobacter baumannii - Zhao, Yining; Liu, Yan; Feng, Luozhu; Xu, Mengxin; Wen, Hong; Yao, Zhuocheng; Shi, Shiyi; Wu, Qing; Zhou, Cui; Cao, Jianming; Zhou, Tieli (Frontiers in Microbiology, 2022)
Acinetobacter baumannii (A. baumannii) is an opportunistic pathogen that is primarily associated with nosocomial infections. With the prevalence of acquired drug resistance, A. baumannii is becoming resistant to traditional antimicrobial drugs and even tend to become resistant the last line of antibiotics, such as colistin. Synergistic combinations of antibiotic and nonantibacterial agent are being regarded as a new alternative therapeutic approach. Chrysin is a component of honey with anti-inflammatory and antioxidant properties. In this study, we evaluated the antibacterial activity of chrysin in combination with colistin against A. baumannii in vitro and in vivo without cytotoxicity. We found that chrysin and colistin had synergistic effects against A. baumannii through damaging the extracellular membrane and changing the membrane potentia of bacteria. The chrysin/colistin combination group was also shown inhibitory effect on the biofilm formation. In conclusion, the synergy between these drugs may allow the use of lower concentrations of colistin for the treatment of A. baumannii infections, thereby reducing dose-dependent side effects. Thus, the combination of chrysin/colistin therapy may provide a new therapeutic option for the control of A. baumannii infections.